2018
DOI: 10.1136/bmjresp-2017-000238
|View full text |Cite
|
Sign up to set email alerts
|

Using domiciliary non-invasive ventilator data downloads to inform clinical decision-making to optimise ventilation delivery and patient compliance

Abstract: IntroductionVentilation parameter data from patients receiving home mechanical ventilation can be collected via secure data cards and modem technology. This can then be reviewed by clinicians and ventilator prescriptions adjusted. Typically available measures include tidal volume (VT), leak, respiratory rate, minute ventilation, patient triggered breaths, achieved pressures and patient compliance. This study aimed to assess the potential impact of ventilator data downloads on management of patients requiring h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 22 publications
(23 reference statements)
0
36
0
5
Order By: Relevance
“…Leaks are responsible for intolerance, nocturnal awakenings, poor compliance, patient–device asynchrony and suboptimal correction of nocturnal respiratory events. Thus, telemonitoring of leaks by the home ventilator software may be very useful and would allow rapid intervention at home should adjustments be required …”
Section: Use Of Niv Data In Different Clinical Situationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Leaks are responsible for intolerance, nocturnal awakenings, poor compliance, patient–device asynchrony and suboptimal correction of nocturnal respiratory events. Thus, telemonitoring of leaks by the home ventilator software may be very useful and would allow rapid intervention at home should adjustments be required …”
Section: Use Of Niv Data In Different Clinical Situationsmentioning
confidence: 99%
“…To date, studies have mainly demonstrated its feasibility in different clinical situations such as initiation of NIV within the home, or to identify changes in clinical status. Most studies are single centre, with short‐term follow‐ups, relatively small sample sizes and driven by expert teams, which limit the representativeness of the results …”
Section: Perspectives For the Future Of Niv Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, different factors influenced the size of this difference depending on the brand of device used . Nevertheless, these data can improve the clinician's ability to recognize potential problems early and intervene . Incorporation of additional signals into the ventilator such as oximetry in conjunction with machine‐derived signals such as airflow and leak can provide valuable information to guide the optimization of therapy, with potentially significant clinical impact …”
Section: Volume‐assured Pressure Supportmentioning
confidence: 99%